Effect of Antiretroviral Therapy to Thyroid Function Status on New Stage 1 and 2 Human Immunodeficiency Virus Patient - Nasution, Melati Silvanni; Lindarto, Dharma; Kembaren, Tambar (Open Access Macedonian Journal of Medical Sciences, 2023)
Background: Thyroid hormone is very important in regulating energy metabolism in all tissues of the human body. Thyroid dysfunction plays an important role in osteoporosis, hyperlipidemia and cardiovascular disease, all of which are associated with Human Immunodeficiency Virus (HIV) infection or therapy for HIV. Medications used to treat HIV infection are also said to be important factors that can cause thyroid abnormalities. This study aim is to see the effect of giving Antiretroviral Therapy (ART) to the thyroid function of new HIV patients in stage 1 and 2. Method: This prospective cohort study was conducted at Medan city health center and Medan Haji Adam Malik Hospital in March-June 2019. HIV patients who met the inclusion criteria were tested for thyroid function (Ft4 and TSH) before and after 3 months on ART, BMI, routine blood, CD4 and quality of life using the SF-36 questionnaire. Data analysis used paired t test and Pearson correlation. Result: 34 patients with stage 1 and 2 HIV showed normal thyroid function ; the average FT4 level was 1.03 ± 0.14 ng / dl and the average TSH level was 1.44 ± 0.68 µIU / mL. After 3 months of antiretroviral therapy, the mean thyroid function changes were obtained from the study subjects, where the mean FT4 results were 0.87 ± 0.13 ng / dl and the average TSH results were 1.76 ± 0.91 µIU / mL and the results were statistically significant with p 0.006 (p <0.05). There was a statistically significant relationship between TSH and CD4 levels with BMI after ART administration (p <0.05), but no statistically significant relationship was found between FT4 and BMI (p = 0.957). No statistically significant relationship was found between CD4 levels in study subjects and changes in fT4 levels (p = 0.557, r = 0.104) and TSH (p = 0.267, r = 0.196). There was also no significant difference in the quality of life of study subjects as seen from the SF-36 questionnaire both from changes in thyroid function and from CD4 levels. Conclusion: Stage 1 and 2 HIV patients who are on ART for 3 months experienced thyroid dysfunction.